Constructing the Idea of Europe through Turkish Media Coverage of the 2016 EU-Turkey Refugee Deal (Decentering European studies: perspectives on Europe from its beyond, 2025)
This chapter tracks how seven Turkish-language news media have covered the EU-Turkey “Refugee Deal” announced in 2016. Using media content as a lens to understand how the idea of Europe is constructed in its periphery, the study identifies themes in the portrayal of Europe, at once pictured as a place of refuge but also as an immoral bargainer betraying its own values. Engaging in the ways in which Europe and the European Union are often conflated in Turkish news media, the study shows that while Europe frequently appears as a haven of progressive values―a place of comfortable living that refugees want to reach at all cost, risking even death―the European Union is regularly represented as an unethical political entity that excludes non-white populations. As an alternative to the conventional approach used by scholars in European studies who examine non-Europeans as constructed “Others,” this research focuses on the representation of Europe from its margins by positioning the Turkish media as an actor in the shaping of a global image of Europe. Thus, this shift encourages a reconceptualization of actors in the peripheries and outside of the continent as actively contributing to the construction of a global vision of Europe.